Minimal inhibitory concentration of seven antimicrobials to Mycoplasma gallisepticum and Mycoplasma synoviae isolates from six European countries. Issue 2 (4th March 2021) - de Jong, Anno; Youala, Myriam; Klein, Ulrich; El Garch, Farid; Simjee, Shabbir; Moyaert, Hilde; Rose, Markus; Gautier-Bouchardon, Anne V.; Catania, Salvatore; Ganapathy, Kannan; Gyuranecz, Miklos; Möller Palau-Ribes, Franca; et al.
ABSTRACT: Mycoplasma gallisepticum and Mycoplasma synoviae are bacterial pathogens that cause disease in poultry, adversely affecting their health and welfare, and are a financial burden on producers. This manuscript describes the results of the MycoPath project that is the first international antimicrobial susceptibility programme for mycoplasma pathogens isolated from poultry. Improved comparative analysis of minimal inhibitory concentration (MIC) results from participating countries was facilitated by using one laboratory determining all MICs. Chicken and turkey isolates were obtained from France, Germany, Great Britain, Hungary, Italy and Spain during 2014–2016. One isolate per farm was retained. The MIC of seven antimicrobial agents was determined using a broth microdilution method, with Friis Medium ( M. gallisepticum ) or Modified Chanock's Medium ( M. synoviae ). Of the 222 isolates recovered, 82 were M. gallisepticum and 130 were M. synoviae. M. gallisepticum MIC50/90 values were 0.12/0.5, 2/8, 0.5/4, 0.12/>64, 0.008/0.062, 0.008/32, 0.062/4 mg/l for doxycycline, enrofloxacin, oxytetracycline, spiramycin, tiamulin, tilmicosin and tylosin, respectively. For M. synoviae, the values were 0.5/1, 8/16, 0.5/1, 0.5/8, 0.25/0.5, 0.062/2 and 0.062/16 mg/l respectively . A bimodal MIC distribution for the fluoroquinolone (enrofloxacin) and the macrolides (spiramycin, tilmicosin and tylosin) indicate that both species have sub-populations that are less susceptible in vitro to those antimicrobials. Some differences in susceptibilities were observed according to host species, Mycoplasma species, and country of origin. This study provides a baseline of novel data for future monitoring of antimicrobial resistance in poultry Mycoplasma species. Additionally, this information will facilitate the selection of the antimicrobial agents most likely to be effective, thus ensuring their minimal use with targeted and correct therapeutic treatments. Highlights First large-scale pan-European collection of representative Mg and Ms isolates. MIC values assessed in central laboratory for Mg and Ms from chickens and turkeys. Range of MIC values for 82 Mg and 130 Ms isolates to seven licenced antibiotics shown. Data can be used to help determine Mg and Ms veterinary-specific breakpoints.